PENINGKATAN KETUNTASAN BELAJAR IPAS SISWA KELAS V SDN 100 MELLE KECAMATAN DUA BOCCOE KABUPATEN BONE MELALUI PENERAPAN MODEL PEMBELAJARAN BILLBOARD RANGKING - Sitti Jauhar; Sudarto , Sudarto; Rusli, Rusli (Bajang Institute, 2025)
This study is a classroom action research that aims to determine whether the application of the billboard ranking learning model can or cannot increase the number of 5th Grade students who achieve mastery in IPAS learning at SDN 100 Melle, Dua Boccoe District, Bone Regency. The subjects of this study were of all the 5th Grade students of SDN 100 Melle, totaling 25 people. The data collection technique used was a test. The data analysis technique used was the percentage technique. Results: in the cycle I the number of students who achieved mastery was of 72% and in the cycle II the number of students who achieved mastery was of 84%. Conclusion: the application of the billboard ranking learning model in IPAS learning can increase the number of the 5th Grade students of SDN 100 Melle, Dua Boccoe District, Bone Regency who achieve mastery